PERAN GURU DALAM PENERAPAN KURIKULUM MERDEKA UNTUK PENINGKATAN KOMPETENSI SISWA SMK: STUDI KASUS DI SMK 1 PERGURUAN CIKINI JAKARTA UTARA (2020–2024) - Sharleen Aulia Redian; Mardi Siswoyo; Khairul Anwar; Marisi Pakpahan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the role of teachers in supporting student competency achievement at SMK 1 Perguruan Cikini Tanjung Priok, North Jakarta, within the context of the implementation of the Merdeka Curriculum from 2020 to 2024. The research employs a qualitative approach using a case study method, allowing for an in-depth exploration of the experiences of both teachers and students in the learning process. Data were collected through interviews, observations, and documentation involving teachers, students, and school management. The findings indicate that teachers play a crucial role as facilitators, motivators, and evaluators in supporting the development of students’ cognitive, psychomotor, and affective competencies. The Merdeka Curriculum offers flexibility for teachers to design project-based learning strategies that are contextualized to industry needs and local characteristics. Although there has been a general improvement in student competencies, the study also reveals several challenges faced by teachers, such as limited training, gaps in technology integration, and the need for stronger institutional support. This research provides practical recommendations to enhance teacher professionalism and adaptive learning strategies to optimize the implementation of the Merdeka Curriculum in vocational schools. The findings are expected to serve as a reference for policymakers in formulating sustainable teacher capacity-building programs.